Functional Characterization of the Osteoarthritis Susceptibility Mapping to CHST11-A Bioinformatics and Molecular Study. - Louise N Reynard; Madhushika Ratnayake; Mauro Santibanez-Koref; John Loughlin (PLoS ONE)
The single nucleotide polymorphism (SNP) rs835487 is associated with hip osteoarthritis (OA) at the genome-wide significance level and is located within CHST11, which codes for carbohydrate sulfotransferase 11. This enzyme post-translationally modifies proteoglycan prior to its deposition in the cartilage extracellular matrix. Using bioinformatics and experimental analyses, our aims were to characterise the rs835487 association signal and to identify the causal functional variant/s. Database searches revealed that rs835487 resides within a linkage disequilibrium (LD) block of only 2.7 kb and is in LD (r2 ≥ 0.8) with six other SNPs. These are all located within intron 2 of CHST11, in a region that has predicted enhancer activity and which shows a high degree of conservation in primates. Luciferase reporter assays revealed that of the seven SNPs, rs835487 and rs835488, which have a pairwise r2 of 0.962, are the top functional candidates; the haplotype composed of the OA-risk conferring G allele of rs835487 and the corresponding T allele of rs835488 (the G-T haplotype) demonstrated significantly different enhancer activity relative to the haplotype composed of the non-risk A allele of rs835487 and the corresponding C allele of rs835488 (the A-C haplotype) (p < 0.001). Electrophoretic mobility shift assays and supershifts identified several transcription factors that bind more strongly to the risk-conferring G and T alleles of the two SNPs, including SP1, SP3, YY1 and SUB1. CHST11 was found to be upregulated in OA versus non-OA cartilage (p < 0.001) and was expressed dynamically during chondrogenesis. Its expression in adult cartilage did not however correlate with rs835487 genotype. Our data demonstrate that the OA susceptibility is mediated by differential protein binding to the alleles of rs835487 and rs835488, which are located within an enhancer whose target may be CHST11 during chondrogenesis or an alternative gene.